Competitive Advantage of Broiler Production in District Mansehra - Khan, Fida Muhammad; Ali, Ghaffar; Sadozai, Khuram Nawaz; Khan, Noor P (Talenta Publisher, 2018)
Poultry is an important sub sector of livestock and is ahead of all other sub sectors in economic growth. Broilers production is a specialized branch of poultry farming. This research was conducted in Mansehra is the region where considerable amount of commercial broiler production takes place. The region of the study has a high concentration of commercial activities, infrastructural facilities like veterinary care as well as climate that favor the production and marketing of poultry meat products. This research was conducted in nine villages of district Mansehra namely Kotli Pain, KotliBala, Kheil, Tanda, Bafa, Chatar Plain, Ahl, Batal and Mongandawraha. The purpose of the research was to analyze the competitive advantage of broiler farming. There were 276 broiler farms in District Mansehra. Simple Random Sampling Technique was used for data collection from 70 respondents. Average total cost of production was found Rs. 738238.11 having average farm size of 3605 broilers. Feed and one day old chick costs constitute 90.01% of the total cost. Average expenditure on production per broiler was Rs. 220.20 having net profit per broiler of Rs. 24.11.Based on Porter study (1990), average variable cost (C) was used as a proxy for competitive advantage. Results of regression analysis show that the main factors that significantly affect competitive advantage of broiler farming in the study area was feed cost, day old chick cost, labor and medication cost while capacity utilization and extension service contacts negatively and significantly affect cost. It means that reducing the above mentioned costs and using installed capacity and extension service contacts will reduce production cost and will promote competitive advantage of broiler production. Broiler production should be encouraged through better feed management practices and also by feeding broilers with nutritious feed. Broiler farmers should be encouraged to fully use their installed capacity of their farm.